2020
DOI: 10.1186/s12951-020-00607-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous delivery of enzalutamide based on high drug loading multifunctional graphene oxide nanoparticles for castration-resistant prostate cancer therapy

Abstract: Background: Enzalutamide (Enz) has shown limited bioavailability via oral administration. Castration-resistant prostate cancer (CRPC) is frequent among patients receiving 18-24 months of androgen deprivation therapy. The nonsteroidal anti-androgen enzalutamide (Enz) used in the treatment of prostate cancer has shown limited bioavailability via oral administration. Therefore, we developed a multifunctional enzalutamide-loaded graphene oxide nanosystem (TP-GQDss/Enz) for CRPC intravenous treatment, with high dru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The utility of combinatorial treatment modalities, specifically radiosensitizers in cancer therapy, was first investigated in the early 1970s [32]. Recently, nanotechnology has paved the way towards the development of an innovative cancer therapy platform [33,34]. Owing to the possibility of modification of nanoparticle composition and surface coating, the functions and specificity of nanoparticles could be more flexibly customized [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The utility of combinatorial treatment modalities, specifically radiosensitizers in cancer therapy, was first investigated in the early 1970s [32]. Recently, nanotechnology has paved the way towards the development of an innovative cancer therapy platform [33,34]. Owing to the possibility of modification of nanoparticle composition and surface coating, the functions and specificity of nanoparticles could be more flexibly customized [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The functionalized GQDs were rapidly internalized by castration-resistant prostate cancer cells via endocytosis, and showed good cancer-targeting ability and when loaded with enzalutamide, they inhibited the growth of C4-2B and LNCaP prostate cancer cell lines in vitro. Moreover, this GQDs nanocarrier showed a controlled drug release, an enhanced cancertargeting ability and alleviated the side effects of drugs, suggesting that the formulation could be utilized in an intravenous therapy for this type of prostate cancer cell [146]. Nitrogen-Doped GQDs Using a combined density functional theory and molecular dynamic approach, Vatanparast and Shariatinia [147] found that among nitrogen-doped GQDs (N-GQDs), the center N-GQDs exhibit improved performance in gemcitabine (GEM, Figure 4) drug delivery compared to that of pristine GQDs and edge N-GQDs.…”
Section: Functionalized Gqdsmentioning
confidence: 98%
“…The functionalized GQDs were rapidly internalized by castration-resistant prostate cancer cells via endocytosis, and showed good cancer-targeting ability and when loaded with enzalutamide, they inhibited the growth of C4-2B and LNCaP prostate cancer cell lines in vitro. Moreover, this GQDs nanocarrier showed a controlled drug release, an enhanced cancer-targeting ability and alleviated the side effects of drugs, suggesting that the formulation could be utilized in an intravenous therapy for this type of prostate cancer cell [ 146 ].…”
Section: Graphene Quantum Dotsmentioning
confidence: 99%
“…Moreover, enzalutamide-loaded materials exhibited excellent cancer-targeting and reserved in vitro progression lines of LNCaP and C4-2B cells of prostate cancer. Additionally, nanocarriers of GQDs revealed an enriched ability of cancer-targeting, a measured drug release, and improved drug side impacts, proposing that it could be applied in the therapy of an intravenous related to this prostate tumor cell type [139]. A variety of different carbon allotropes applied in cancer therapy are provided in Table 1.…”
Section: Functionalized Gqdsmentioning
confidence: 99%